2022
DOI: 10.1093/rheumatology/keac367
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in the prediction of gout flares: a 12-month prospective observational study

Abstract: Objectives To evaluate whether ultrasound (US) findings indicating monosodium urate (MSU) deposits and US-detected inflammation [i.e. power Doppler (PD) signal] predict gout flares over 12 months. Methods Gout patients on urate-lowering therapy for at least the preceding six months were enrolled consecutively in this 12-month prospective, observational, single-centre study. A nested case-control analysis was performed. Cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Katz et al suggested that MSU crystals may be deposited on the synovium of medium vessels, particularly in the active phase 25 . Cipolletta et al observed that MSU burden and inflammation detected by US were independent predictors of gout lasting longer than 12 months 26 . In addition, flares should be carefully prevented in patients with a high MSU deposition burden, especially DCS and tophi and inflammation detected by US.…”
Section: Discussionmentioning
confidence: 99%
“…Katz et al suggested that MSU crystals may be deposited on the synovium of medium vessels, particularly in the active phase 25 . Cipolletta et al observed that MSU burden and inflammation detected by US were independent predictors of gout lasting longer than 12 months 26 . In addition, flares should be carefully prevented in patients with a high MSU deposition burden, especially DCS and tophi and inflammation detected by US.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional analysis of data from consecutive patients acquired during two prospective cohort studies8 9 and a cross-sectional case–control study10 between September 2019 and June 2022 was carried out at the Polytechnic University of Marche (Ancona, Italy). Data collection and study’s hypothesis were planned before the index test and reference standard were performed.…”
Section: Methodsmentioning
confidence: 99%
“…US assessments were carried out according to the 2017 EULAR standardised procedures for US imaging in rheumatology11 by a rheumatologist blinded to patients’ diagnosis 8–10…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations